The Dilemma of Modernity: Value Conflict in The Application of Customary Criminal Law in Multicultural Society: Dilema Modernitas: Konflik Nilai dalam Penerapan Hukum Pidana Adat pada Masyarakat Multikultural - Lubis, Rahmad; Helvis, Helvis; Purnama, Desi; Yunus, Nur Rohim; Shapiulayevna, Aliyeva Patimat (al Hairy | Journal of Islamic Law, 2025)
Modernity has brought significant changes in social, cultural, and legal structures in various parts of the world, including in multicultural societies. One of the main challenges that arise is the conflict of values in the application of customary criminal law. Customary criminal law, which has long been an integral part of traditional people's lives, now faces pressure from a modern legal system that tends to be universal and based on human rights. This study aims to analyze the dilemmas arising from the tension between the two legal systems, focusing on how customary criminal law is applied in a multicultural society, where diverse cultural and religious values often clash. In this context, the application of customary criminal law often faces challenges in maintaining a balance between maintaining local values and accommodating the principles of modernity, such as gender equality, individual rights, and social justice. This research suggests the need for a more inclusive and dialogical approach between customary law and state law in order to create a legal system that is responsive to cultural diversity, without neglecting the basic principles of human rights.